Pengaruh Pembagian Kerja dan Wewenang terhadap Kinerja Perawat di Rumah Sakit Umum Mitra Sejati - Nurul Faradila; Yamin Siregar; Isnaniah LKS (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2020)
This study aims to find out and prove "The Effect of Division of Work and Authority on Nurse Performance at the True Partner General Hospital" This type of research is associative which is a question of the relationship between two variables. The data analysis technique uses multiple linear analysis with hypothesis testing using t test, f test and coefficient of determination. the results of the discussion and conclusions indicate that the division of labor and authority partially and simultaneously has a positive and significant effect on the performance of nurses at the Mitra Sejati General Hospital